PERTUMBUHAN BAWANG MERAH (Allium cepa var. Bauji) PADA TANAH GAMBUT DENGAN PENAMBAHAN TRICHO-KOMPOS KOTORAN BEBEK - Nova, Nova; Zakiah, Zulfa; Mukarlina, Mukarlina (Universitas Tanjungpura, 2020)
Shallots (Allium cepa var. Bauji) are plants that are included in the Liliaceae family. The dominance of peatlands in West Kalimantan is one of the factors causing the low production of shallot plants. This study aims to determine the effect and concentration of duck manure tricho-compost (TKB) on the growth of shallot plants in peatlands. The research was conducted from July to October 2019. The compositions used included distilled water, bran, dolomite, sugar, potato, duck dung, urea, TSP and KCL, Trichoderma harzianum isolates, liquid Trichoderma starter, peat soil, and shallot bulbs (Allium cepa var. Bauji). The study used a completely randomized design with six treatments in the form of negative control (-); 50 g of TKB; 100 g of TKB; 200 g TKB; 400 g TKB and positive control (+). The results showed that there was a significant effect between the application of tricho-compost duck manure on growth parameters. Tricho compost treatment with 100 g of duck manure was the concentration with the best results on the growth of shallots, with a height of 28.88 cm, number of leaves 19.88, total wetness of 15.99 g, wet tuber weight 5.37 g and wet root weight 0.69 g.